REMEDIASI MISKONSEPSI MENGGUNAKAN MODEL LEARNING CYCLE 7E PADA MATERI PESAWAT SEDEHANA DI SMP - Febri Riski Satriana; Haratua Tiur Maria S.; Hamdani Hamdani (Universitas Tanjungpura, 2019)
AbstractThis study aims to determine whether student’s misconceptions remediation using the 7E learning cycle model effective to reduce the number of student’s who exprecience misconceptions on simple machines in Junior High School 9 Pontianak. The method that used in this study is experiment study method with type Pre-Experimental Design study with plan model One Group Pretest-Posttest Design study. The technology removal of the example that used in this study is intact group technique and it is obtained at VIII C class that consist of 39 students. The instrument of this study is diagnostic test that consist of 9 multiple choice questions. Based on the data analysis, mean percentage descent numbers of the student's misconceptions is about 79,16%. The result of the statistic test Mc Nemar with dk = 1 and α = 5% showed > this result of test Mc Nemar show that have happened conceptual change on the students significantly. Cost of the normalised gain 7E learning cycle model in remediate student’s misconceptions is 0,78 (high category). The result of this study expected can be used as one of the alternative in remediation student’s misconceptions activity. Keywords: Remediation, Misconceptions, Learning Cycle 7E, Simple Machine